2018
DOI: 10.1002/mp.12877
|View full text |Cite
|
Sign up to set email alerts
|

Automatic intraoperative stitching of nonoverlapping cone‐beam CT acquisitions

Abstract: Purpose Cone-Beam Computed Tomography (CBCT) is one of the primary imaging modalities in radiation therapy, dentistry, and orthopedic interventions. While CBCT provides crucial intraoperative information, it is bounded by a limited imaging volume, resulting in reduced effectiveness. This paper introduces an approach allowing real-time intraoperative stitching of overlapping and non-overlapping CBCT volumes to enable 3D measurements on large anatomical structures. Methods A CBCT-capable mobile C-arm is augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The goal of DFO is to restore the balance of loading between two compartments of the knee. 22 , 23 Performing DFO for correcting valgus deformity is a good surgical option for severe cases. 2 , 24 , 25 Shivji et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of DFO is to restore the balance of loading between two compartments of the knee. 22 , 23 Performing DFO for correcting valgus deformity is a good surgical option for severe cases. 2 , 24 , 25 Shivji et al .…”
Section: Discussionmentioning
confidence: 99%
“…The goal of DFO is to restore the balance of loading between two compartments of the knee. 22,23 Performing DFO for correcting valgus deformity is a good surgical option for severe cases. 2,24,25 Shivji et al 26 reported that 86 patients with an average age of 48 years were treated with DFO due to valgus knee deformity combined with lateralcompartment OA.…”
Section: Advantage Of Dfo Modeling Based On Cadmentioning
confidence: 99%
“…The mean separation of our UTTs, at 9.9 cm, facilitated a minimal TRE. Ensuring that the UTT registration spheres lie completely within the CBCT volume (in this study, 25 × 25 × 18 cm) may be challenging in obese patients or those with large, deep tumors; however, 1 possible solution would be to automatically stitch together 2 acquisitions to encompass a larger volume 40 . Using 1 UTT provided wide coverage but the spheres did not encircle the target, leading to a higher TRE of >1 mm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With the availability of 3D intra-operative imaging, instead of 2D X-ray image stitching, recent works suggested stitching of tomographic volumes reconstructed from X-ray images acquired on a circular trajectory [10,9]. While volumetric data do not suffer from the effects of parallax and can, therefore, be stitched easily, circular shortscans required for 3D tomographic reconstruction expose the patient to much higher radiation doses compared to simple X-ray acquisitions, suggesting that these methods are best employed only once, e.g., for verification.…”
Section: Related Workmentioning
confidence: 99%